Implementation Of The Absolute Responsibility Statement Letter For The Truth As Husband And Wife In The Issuance Of Birth Certificates From The Perspective Of Maqasid Al-Syari’ah - Muhammad, Hanifah Salma; Farah, Dena Nabila; Ibrahim, Malik; Abdullah, Raihanah Binti Haji (Hukum Islam, 2025)
The legal relationship between parents and children is usually proven by a birth certificate, so a birth certificate must be issued for the child. This is as stated in Article 27 paragraphs (1) and (2) of Law Number 23 of 2002 concerning Child Protection which confirms that a child's identity must be given from birth and this identity is stated in the form of a birth certificate. Yogyakarta Dindukcapil is the agency tasked with issuing birth certificates for Yogyakarta residents. One of the requirements for applying for a child's birth certificate is to attach a marriage certificate or marriage book from both parents. If the parents cannot show the marriage certificate, they can attach a statement of absolute responsibility for the truth as husband and wife. It is interesting to carry out research on the implementation of the statement of absolute responsibility for the truth of husband and wife in the Yogyakarta Dindukcapil Office. This type of research is field research using the Maqasid al-Syari'ah approach. The data analysis method used is descriptive analytical using data collection and analysis methods in the form of interviews, observation and documentation. The results of the research show that the implementation of the statement of absolute responsibility in Yogyakarta Dindukcapil is intended for married couples who married before the existence of Law Number 1 of 1974 concerning Marriage. According to Islamic law, the implementation of the absolute responsibility statement in Yogyakarta Dindukcapil is in accordance with Maqasid al-Syari'ah (The objectives of Islamic law) namely Hiifz ad-din, Hiifz an-Nasl, and Hiifz al-Mal.